2012
DOI: 10.5194/acp-12-1541-2012
|View full text |Cite
|
Sign up to set email alerts
|

Observation and modelling of OH and HO<sub>2</sub> concentrations in the Pearl River Delta 2006: a missing OH source in a VOC rich atmosphere

Abstract: Abstract. Ambient OH and HO2 concentrations were measured by laser induced fluorescence (LIF) during the PRIDE-PRD2006 (Program of Regional Integrated Experiments of Air Quality over the Pearl River Delta, 2006) campaign at a rural site downwind of the megacity of Guangzhou in Southern China. The observed OH concentrations reached daily peak values of (15–26) × 106 cm−3 which are among the highest values so far reported for urban and suburban areas. The observed OH shows a consistent high correlation with j(O1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
289
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(344 citation statements)
references
References 104 publications
52
289
3
Order By: Relevance
“…Our results suggest that in the fresh plumes, the vertical transport predominates with the oxidative capacity reaching its maximum at 1,000 m. In the flight tracks classified as BG, we observed the widest variation in the average OH concentration using the new sequential reaction model (Figure 9, on bottom), especially in upper levels (0.5 -1  10 6 molecules cm -3 ), although reported a lower confidence level in this presented an increase near to CL (~1,000 m), in agreement with previous studies (Karl et al, 2007;Kuhn et al, 2007;Langford et al, 2005;Mauldin et al, 1997). Several studies investigated the uncertainties in the isoprene oxidation mechanism, and most of them focus on OH concentration levels through observational and modeling studies (de Gouw et al, 2006;Kubistin et al, 2010;Kuhn et al, 2007;Lelieveld et al, 2008;Lu et al, 2012;Whalley et al, 2014;Yokelson et al, 2007). Under a high isoprene and low-NO atmospheric regime, there is a controversial discussion about the impact on the oxidative capacity in forest sites.…”
Section: Oh Predicted Using Sequential Reaction Approachsupporting
confidence: 73%
“…Our results suggest that in the fresh plumes, the vertical transport predominates with the oxidative capacity reaching its maximum at 1,000 m. In the flight tracks classified as BG, we observed the widest variation in the average OH concentration using the new sequential reaction model (Figure 9, on bottom), especially in upper levels (0.5 -1  10 6 molecules cm -3 ), although reported a lower confidence level in this presented an increase near to CL (~1,000 m), in agreement with previous studies (Karl et al, 2007;Kuhn et al, 2007;Langford et al, 2005;Mauldin et al, 1997). Several studies investigated the uncertainties in the isoprene oxidation mechanism, and most of them focus on OH concentration levels through observational and modeling studies (de Gouw et al, 2006;Kubistin et al, 2010;Kuhn et al, 2007;Lelieveld et al, 2008;Lu et al, 2012;Whalley et al, 2014;Yokelson et al, 2007). Under a high isoprene and low-NO atmospheric regime, there is a controversial discussion about the impact on the oxidative capacity in forest sites.…”
Section: Oh Predicted Using Sequential Reaction Approachsupporting
confidence: 73%
“…[22][23][24] Even more troubling is that, contrary to expectations, noon-time _OH concentrations (in Birmingham) during winter were found to be only a factor of 2 smaller than in summer, despite a factor of 15 reduction in J(O 1 D) over the same period. 25 Given the key role of _OH, this represents a major deciency in our understanding of tropospheric chemistry.…”
Section: 21415mentioning
confidence: 46%
“…detected at a pristine site yearlong, 21 and episodically at a polluted one, 22 is not well reproduced by standard chemical models. [22][23][24] Even more troubling is that, contrary to expectations, noon-time _OH concentrations (in Birmingham) during winter were found to be only a factor of 2 smaller than in summer, despite a factor of 15 reduction in J(O 1 D) over the same period.…”
Section: 21415mentioning
confidence: 99%
“…Based on a steady-state approach for OH, Hofzumahaus et al (2009) compared the known production and destruction rates of OH by taking measured concentrations of OH, HO 2 , NO and the total OH reactivity of ambient air. It was concluded that during a field campaign in the Pearl River Delta in southern China, the conventional OH recycling rate by HO 2 + NO was too small by a factor of three to explain the measured OH under low-NO conditions Lu et al, 2012).…”
Section: S Nehr Et Al: Atmospheric Photochemistry Of Aromatic Hydromentioning
confidence: 99%
“…In contrast, RO 2 has to be converted to HO 2 first which requires at least one additional O 2 reaction following the RO 2 + NO reaction. This RO 2 -to-HO 2 conversion is accomplished in a pre-reactor (Fuchs et al, 2008 Lu et al, 2012). was then reduced to 0.17 by means of technical changes of the experimental setup .…”
Section: Appendix A: Correction Of Ho 2 Measurement Interferencesmentioning
confidence: 99%